Two new species of Leptolaimus (Nematoda: Plectida) from Chinese sea area - Gu, Huimin; Sun, Lingyun; Huang, Yong (Zootaxa, 2024)
Two new Leptolaimus species from the Chinese sea area are described and illustrated. Leptolaimus gracilis sp. nov. is characterized by rounded labial region offset from body contour; cephalic setae 5–6 µm long; males with eight tubular and without alveolar supplements, tubular supplements sickle-shaped with pointed tips; spicules arcuated and about 18 µm long; gubernaculum with straight dorso-caudal apophysis; female without supplements, vulva midventral; tail elongate conical. The new species can be easily identified from other known species by males with eight sickle-shaped supplements with pointed tips and the spacing of adjacent supplements almost equal except that of the most anterior two supplements. Leptolaimus hamatus sp. nov. is characterized by small body size; cephalic setae 2–3 µm long; amphidial fovea located 2.6–3.3 times of head diameter from anterior end; male with six tubular and without alveolar supplements, tubular supplements hooked distally; spicules slightly curved, knife-like, 22–24 µm long; gubernaculum with straight dorso-caudal apophysis; females without supplements, vulva situated at right subventral side of body, tail conico-cylindrical.